Pre-recorded video lectures versus live online lectures: a comparison of students’ performance - Jamaluddin, Junaidah; Mahali, Mahathir; Nias Ahmad, Mohamad Azmi; Mohd Din, Norlaila; Hashim, Azizi @ Hamizi (GADING Journal for the Social Sciences, 2025)
The COVID-19 pandemic that led to the shutdown of classrooms throughout the world, has increased reliance on online forms of instruction. One of the efforts done to make online instruction a near equivalent to face-to-face instruction is the provision of pre-recorded video lectures (PRVL) and live online lectures (LOL). During the post-pandemic era, the use of these online learning instructions continues to evolve and expand, highlighting both opportunities and challenges. This research paper examines whether the PRVL has the same effect on students‟ performance compared to LOL. Students‟ performance is further analysed based on the six cognitive levels of Bloom‟s Taxonomy to compare the score differences across all levels between two groups of students instructed using PRVL and LOL. The target sample group for this study consisted of 134 Diploma in Accountancy students enrolled in the “Financial Accounting 4” (FAR270) course at Universiti Teknologi MARA Pahang Branch during the academic session from March to July 2021. The students were divided into two groups: the PRVL group (68 students) and the LOL group (66 students). The assessment questions were administered to both groups after the completion of each topic. The results of the study show that PRVL helped students to perform better in their overall assessments in comparison to LOL. It was also found that the PRVL group performed better on moderate and high cognitive level of questions. On the contrary, the LOL group outperformed the PRVL group on lower-order thinking questions. However, no significant difference was found between the PRVL and LOL groups for “remembering” questions. It is crucial to evaluate students‟ achievement in different cognitive levels of questions for these two online learning methods, as this allows educators to implement appropriate strategies to improve students‟ learning outcomes.